Propriedades de medidas dos instrumentos de avaliação de atividade física em indivíduos portadores de doença renal crônica: uma revisão sistemática - Stella, Thamiê Cristina (2023)
INTRODUCTION: In chronic kidney disease (CKD), there are several studies that assess physical activity through patient-reported outcome measures (PROMs), but with large heterogeneity in the tool’s choice. OBJECTIVES: To identify, evaluate and synthesize the psychometric properties of PROMs used to assess physical activity in the CKD population. METHODOLOGY: A systematic review was carried out in PubMed, SciELO, Medline, Lilacs and EMBASE databases. The descriptors used: Chronic Kidney Disease, Chronic Renal Insufficiency, Chronic Kidney Failure, Physical Activity, Physical Activities, Psychometrics, Patient Outcome Assessment, Outcome Assessment, Health Care, Reproducibility of Results, Reliability of Result, Validity of Result, Reliability and Validity, Test Retest Reliability, Validity, Face, Finding Reproducibility, Validation studies, Cross Cultural Comparison; with boolean operators AND or OR. The quality of the studies was assessed by COSMIN RoB and EMPRO. RESULTS: 13,638 studies were found, with 15 included in the end. Of the 11 PROMs found, 2 are specific to CKD. Human Activity Profile (HAP) was the non-specific PROM with the best performance, while Chronic Kidney Disease Physical Activity Questionnaire (CKD-PAQ) was the only PROM with a satisfactory result in assessment’s tools. COSMIN RoB and EMPRO presented disagreements in 5 PROMs. CONCLUSION: There is no consensus on the best PROM to assess physical activity in CKD. HAP and CKD-PAQ are the PROMs that indicate better performance. The divergences between COSMIN RoB and EMPRO demonstrate that the choice of assessment tool depends on the evaluator's expertise and objective. More research on the topic is needed, especially in the milder stages of CKD.